PERAN FOOD AND AGRICULTURE ORGANIZATION (FAO) DALAM MENANGANI KRISIS PANGAN DI ETHIOPIA - Windy Andini Ekaputri; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research attempts to explain and describe the role of Food and Agriculture Organization in overcoming the food crisis in Ethiopia. As an international organization which focus in food and agriculture, FAO has been involved in dealing with food crisis in Ethiopia as a result of  uncertain climate change and poor environmental management. The researcher used the concept of international organization and food security to analyze the role of FAO as a facilitator to maintain the stability of food access by increase production by utilizing natural resources, conducting community empowerment training programs and as initiator to got cooperation with states, international organization, or other actor to guarantee the fulfillment of food availability.Data of this research was obtained from the books, journals, official documents and websites that support the hypothesis. The author used interest group level analyze and this research is using Pluralism perspective and international organization theory. This reasrch also using concept of food crisis. In this study, the authors found that FAO provided assistance to Ethiopia in the form of policy making, natural resource management, land administration, crop and livestock production and agribusiness development. FAO also provides assistance in the form of funds used to implement 3 priority focus areas for CPF. From this FAO assistance, Ethiopia can implement programs that benefit mainly food livestock and fisheries Keywords : Food Crisis, FAO, CPF, Ethiopia